The body in culture, technology and society - Shilling, Chris (London ; Thousand Oaks, Calif. : SAGE, 2005)
This is a milestone in the sociology of the body. The Body in Culture, Technology and Society offers the most comprehensive overview of the field to date and an innovative framework for the analysis of embodiment. It is founded on a revised view of the relation of classical works to the body.
Cover; Contents; Acknowledgements; Chapter 1 -- Introduction; Chapter 2 -- Classical Bodies; Chapter 3 -- Contemporary Bodies; Chapter 4 -- Working Bodies; Chapter 5 -- Sporting Bodies; Chapter 6 -- Musical Bodies; Chapter 7 -- Sociable Bodies; Chapter 8 -- Technological Bodies; Chapter 9 -- Conclusion; Bibliography; Author Index; Subject Index.
Includes bibliographical references (pages 210-234) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Human body -- Social aspects; Corps humain -- Aspect social; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Human body -- Social aspects; Kultur; Technologie; Gesellschaft; Körper; Menselijk lichaam; Sociologische aspecten; Sociale aspecten; Körper -- Soziales